Development and Effectiveness of eBizmate: A Project-Based Digital Simulation for Enhancing Business Opportunity Analysis Competence in Vocational Education - Ardyanti, Yuanita; Yusuf, Arief Rahman; Sumaji, Sumaji; Talib, Corrienna Abdul (Journal of Nonformal Education, 2026)
Background – Competency in analyzing business opportunities is a fundamental component of the Entrepreneurship and Crafts (PKWU) subject in the Indonesian curriculum. However, students often experience difficulties due to the abstract and complex nature of business analysis concepts, particularly in market, financial, and risk analysis. Research Objective – This study aims to develop and examine the effectiveness of EBizmate, an interactive digital learning media designed as a project-based business simulation platform, to enhance students’ competence in analyzing business opportunities. Research Method – This study employed a Research and Development (R&D) approach using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The developed media was validated by experts in learning media, subject matter, and instructional design. Effectiveness testing was conducted using a quasi-experimental design involving 60 vocational high school students. Research Findings – The results indicated a significant improvement in business analysis competence among students using eBizmate. The experimental group achieved an N-Gain score of 0.64 (p < 0.001), which was higher than the control group’s N-Gain score of 0.34, with a large effect size (Cohen’s d = 1.21). These findings demonstrate that eBizmate effectively enhances students’ abilities in market analysis, financial analysis, and risk assessment. Research Conclusion – The study concludes that eBizmate is a valid, practical, and effective digital learning medium for supporting experiential learning and structured scaffolding within the Project-Based Learning (PjBL) framework in vocational entrepreneurship education. Research Novelty/Contribution – This research contributes an empirically validated model for integrating simulation-based digital learning media with Project-Based Learning to improve business opportunity analysis competence in vocational high school entrepreneurship education.